2020
DOI: 10.1111/tran.12414
|View full text |Cite
|
Sign up to set email alerts
|

The desert as laboratory: Science, state‐making, and empire in the drylands

Abstract: was awarded a US$3.9 million contract from the Sultanate of Oman to develop research laboratories for the country's "One Million Date Palms for Oman" initiative. This project is only the most recent example of a much longer set of collaborations between actors in the two regions, which began when Omani date palms were imported to the University of Arizona's Agriculture Experiment Station in the 1890s. In tracing this history, I show how establishing state power in the US West was facilitated by the work of sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
9
0
3
Order By: Relevance
“…Beyond a focus specifically on infrastructure, Aya Nassar engages with dust as both a ‘material and an imaginative metaphor that assembles architecture, urban space, archives, and histories’ (2018, p. 412). For Natalie Koch (2021), the scientific connections between Arizona and the Arabian Peninsula reveal the relationships between imagination, materiality, and geopolitics that occur beyond a purely state‐centric geopolitical framework. This paper's focus on a cultural and leisure infrastructure, and the unique relationships between materiality and imagination on walking trails, enables this paper to attend to the relationship between colonialism and infrastructure anew.…”
Section: The ‘Infrastructure Turn’ Colonial Temporalities and Intimacymentioning
confidence: 99%
“…Beyond a focus specifically on infrastructure, Aya Nassar engages with dust as both a ‘material and an imaginative metaphor that assembles architecture, urban space, archives, and histories’ (2018, p. 412). For Natalie Koch (2021), the scientific connections between Arizona and the Arabian Peninsula reveal the relationships between imagination, materiality, and geopolitics that occur beyond a purely state‐centric geopolitical framework. This paper's focus on a cultural and leisure infrastructure, and the unique relationships between materiality and imagination on walking trails, enables this paper to attend to the relationship between colonialism and infrastructure anew.…”
Section: The ‘Infrastructure Turn’ Colonial Temporalities and Intimacymentioning
confidence: 99%
“…Urban and regional research has shown interest in the notion of experiment by investigating a multiplicity of experimental practices that strive to provide solutions for social governance, regional development or urban sustainability. Experimental methods have proven to be attractive in areas as diverse as climate change mitigation (Bulkeley and Broto, 2013; Karvonen, 2018), sustainable urbanism (Hodson and Marvin, 2007; Marres, 2009; Evans, 2011; Evans and Karvonen, 2014), landscape and housing design (Strebel and Jacobs, 2014; Lokman, 2017), regional economic growth (Marvin and Silver, 2016; Koch, 2021), facilitation of social encounters (Mayblin and Valentine, 2015), and management of racial others (Chamberlain, 2020). Such practices all point to the growing importance of open‐ended interventions as a means to transform places into sites of knowledge production, instead of just the application of existing knowledge (Evans, 2011; Bulkeley and Broto, 2013; Karvonen and van Heur, 2014).…”
Section: Laboratory Theory Field Experiments and Surprise As Bases Of...mentioning
confidence: 99%
“…III From the treetops to the bedrock Geographies of technoscience are increasingly taking landscapes and biomes like deserts (Koch, 2021) ice sheets (Bruun, 2020) or oceans (Lehman, 2018) as the starting point of analyses, rather than (or perhaps in addition to) the classic spatial repertoire of laboratory or field. Starting from these more-thanhuman realms reflects a growing concern with how sciences like ecology are implicated in the management, exploitation and protection of environments across an increasingly diverse set of geographies (e.g.…”
Section: Zoning Sciencementioning
confidence: 99%
“…Relevant here is Andrew Barry’s notion of ‘technological zones’: these are spaces of compatible technique and procedure where forms of measurement, assessment, qualification and circulation are given increasingly standardised forms (Barry, 2006). Frequently these zones of technological and infrastructural compatibility extend beyond the borders of nation-states, and are co-produced with new spatialities of (geo)political power (Barry, 2001; Koch, 2021). But a technological zone is not a social structure or a disciplinary institution – a zone is rather an ‘assemblage that accelerates and intensifies agency [both human and nonhuman] in particular directions, and with unpredictable and dynamic effects’ (Barry, 2006: 241).…”
Section: Zoning Sciencementioning
confidence: 99%